COMPLEX ORAL REHABILITATION BY IMPLANT PROSTHETIC MEANS IN SEVERE ATROPHIC MAXILLA - Amalia Tofan; Andra-Ana Serban; Ioana Deris; Agop-Forna Doriana; Bujor Emanuela; Norina Forna (Romanian Journal of Medical and Dental Education)
Management of patients with severely atrophic maxilla has long been a treatment challenge for our specialty. The advent of zygomatic implants in 1988 by Branemark led to an alternative treatment modality for patients with maxillary defects and those with severely resorbed alveolar ridges. Over the past two decades, several implant and treatment advances have been made to improve treatment planning placement, and restoration of the severely atrophic maxilla, making zygomatic implants a first-line treatment option in these situations.